COMPARATIVE CHARACTERISTICS OF MORPHOFUNCTIONAL CHANGES IN THE THYROID GLAND IN EXPERIMENTAL RHEUMATOID ARTHRITIS (Journal of Universal Science Research, 2024)
Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disorder primarily affecting the joints. However, growing evidence suggests that RA can also impact extra-articular tissues, including the thyroid gland. The thyroid gland plays a crucial role in regulating metabolism through the production of thyroid hormones, and its dysfunction can lead to significant health implications. Understanding the morphofunctional changes in the thyroid gland in the context of RA is essential for improving clinical management and outcomes in affected patients.